Evaluasi Program Pembaca Baru Alkitab (PBA) Lembaga Alkitab Indonesia (LAI) Di Kabupaten Sumba Barat - Merry Bendelina Asalaka; Bambang Suteng Sulasmono; J.T. Lobby Loekmono (Universitas Kristen Satya Wacana, 2019)
The research aim is to evaluate the implementation of the New Bible Readers (Pembaca Baru Alkitab/ PBA) program by the Indonesia Bible Institute (Lembaga Alkitab Indonesia/ LAI) which is conducted in the West Sumba district. This evaluative research applies the qualitative descriptive method with CIPP as the evaluation model. The research subjects are the Head of Surveyor and Evaluator, Program Manager, Field Head Staff, Regional Coordinator, and Tutor. The data collection is the interview, observation, and documentation study. The data validation was obtained through the method and data source triangulation. Furthermore, the data were analyzed by conducting data reduction, data presentation, and verification. The evaluation result on the Context Components reveals that the PBA LAI program is required by the congregation of churches in West Sumba. The Input Components of PBA LAI program was constructed systematically and directed to answer the needs of the stakeholders and the congregation’s literacy state. The programs were supported by competent human resources in accordance with the criteria set and prepared with training, facilities and budget that support the program implementation for one year, and the required procedures and regulations. The Process Component shows that the whole planned programs have been carried out successfully. However, the result shows that the main obstacle in the implementation of the program was the learning process that ran out of the planned schedule. In addition, there was a lack of supervision by the regional coordinator that didn’t go as planned. On the Product Component, shows that the PBA LAI program has given a positive impact in accomplishing the goal of the citizens have learned basic literacy (reading, writing, and counting) within the short term goal, as for the long term goal. And as the long term goal, the congregation has learned to take part and improve their role in serving the church. Lastly, based on the results above, the writer would like to give a suggestion to the Program Manager to execute sufficient program developments and improve the program quality for the program sustainability.